2020
DOI: 10.1101/2020.08.06.239889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parietal Contributions to Abstract Numerosity Measured With Steady State Visual Evoked Potentials

Abstract: Non-symbolic number changes produce transient Event Related Potentials over parietal electrodes, while numerosity effects measured with Steady-State Visual Evoked Potentials (SSVEPs) appear to originate in occipital cortex. We hypothesized that the stimulation rates used in previous SSVEP studies may be too rapid to drive parietal numerosity mechanisms. Here we recorded SSVEPs and behavioral reports over a slower range of temporal frequencies than previously used. Isoluminant dot stimuli updated at a consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Deviants were designed as standards except that the magnitude of one feature (total area, convex hull, numerosity, dot size, and density) was increased by a factor of 150%. Previous experimental parameter manipulations in SSVEPs with nonsymbolic material have demonstrated that the direction of the change did not impact the oddball frequency responses to numerosity changes ( Kohler et al. 2020 ).…”
Section: Methodsmentioning
confidence: 95%
“…Deviants were designed as standards except that the magnitude of one feature (total area, convex hull, numerosity, dot size, and density) was increased by a factor of 150%. Previous experimental parameter manipulations in SSVEPs with nonsymbolic material have demonstrated that the direction of the change did not impact the oddball frequency responses to numerosity changes ( Kohler et al. 2020 ).…”
Section: Methodsmentioning
confidence: 95%
“…Then the EEG signals were re-referenced to the common average of all channels and segmented into 1.17-s epochs. Epochs with more than 10% of time samples exceeding threshold (30 -80 μV) were excluded further on a channel-by-channel basis 69 .…”
Section: Eeg Acquisitionmentioning
confidence: 99%
“…Epochs with more than 10% of time samples exceeding threshold (30 -80 μV) were excluded on a channelby-channel basis 71 . S2 shows the number of epochs (1.1667-s each) we acquired before and after data pre-processing summing across all five categories.…”
Section: Pre-processingmentioning
confidence: 99%
“…To identify and compare overall response amplitude across harmonics, we computed the root sum of squares (henceforth referred to as RSS projected amplitude) by projecting each complex-valued data point onto the mean vector (55, 56), and then computing the square root of summed squared amplitudes across multiple harmonics (57, 58).…”
Section: Eeg Preprocessing and Analysismentioning
confidence: 99%